2003
DOI: 10.1007/s00216-002-1714-z
|View full text |Cite
|
Sign up to set email alerts
|

Highly sensitive and selective spectrophotometric method for determination of trace gold in geological samples with 5-(2-hydroxy-5-nitrophenylazo)rhodanine

Abstract: A excellent sensitive and selective method for spectrophotometric determination of trace gold has been developed, the method is based on the color reaction of gold(III) with new reagent 5-(2-hydroxy-5-nitrophenylazo)rhodanine (HNAR). Under optimal conditions, HNAR reacts with gold(III) to form a 1:5 orange complex, which has an maximum absorption peak at 480 nm. Maximum enhancement of the absorbance of the complex was obtained in the presence of the mixed surfactant of Triton X-100 and CTMAB; the reaction comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 29 publications
0
10
0
Order By: Relevance
“…The arylidene derivatives of rhodanine have also broad biological activities, including antiviral, antimicrobial, cardiac, anti‐inflammatory, and antifungal effects . Some of the rhodanine‐based compounds have been used to determine and extract of the metal cations from standard or sample solutions . For example, Liu et al reported the synthesis and application of rhodanine‐bonded silica gel for the preconcentration and separation of Ag(I), Au(III), and Pd(II) ions.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The arylidene derivatives of rhodanine have also broad biological activities, including antiviral, antimicrobial, cardiac, anti‐inflammatory, and antifungal effects . Some of the rhodanine‐based compounds have been used to determine and extract of the metal cations from standard or sample solutions . For example, Liu et al reported the synthesis and application of rhodanine‐bonded silica gel for the preconcentration and separation of Ag(I), Au(III), and Pd(II) ions.…”
Section: Introductionmentioning
confidence: 99%
“…13 Some of the rhodanine-based compounds have been used to determine and extract of the metal cations from standard or sample solutions. [13][14][15][16] For example, Liu et al reported the synthesis and application of rhodanine-bonded silica gel for the preconcentration and separation of Ag(I), Au(III), and Pd(II) ions. The results showed that trace amounts of the metal ions can be efficiently adsorbed by rhodanine-bonded silica gel from acidic solution without interfering common coexisting ions to the preconcentration and determination.…”
mentioning
confidence: 99%
“…A simple sensitive and selective method for determination of trace gold has been required. Sophisticated techniques, such as inductively coupled plasma mass spectrometry (ICP-MS) ( Juvonen et al 2002 ), inductively coupled plasma atomic emission spectrometry (ICP-AES) ( Wu et al 2004 ), electrochemical ( Kavanoz et al 2004 ), spectrophotometry ( Zaijun et al 2003 ), neutran activation analysis ( Nat et al 2004 ) and atomic absorption spectrophotometry (AAS) ( Medved et al 2004 ) have widely been applied to the determination of gold in various samples. Some factors such as initial cost of instrument, technical know-how, consumable and costly maintenance of technique restrict the wider applicability of these techniques, particularly in laboratories with limited budget in developing countries and for field work.…”
Section: Introductionmentioning
confidence: 99%
“…18 The method also does not require the use of a surfactant. 16 Conditions: 1.0´10 -4 mol L -1 DATI; pH 3; l = 10 mm.…”
Section: Discussionmentioning
confidence: 99%
“…Separation and preconcentration steps are frequently required for the determination of gold. [3][4][5][6][7][8] Spectrophotometry is often used for gold determination in combination with various organic reagents, such as 5-(4-carboxylphenyl-azo)-8-hydroxyquinoline, 9 5-(4-carboxylphenylazo)-8-aminoquinoline, 10 5-(p-amino-benzylidene)-thiorhodanine, 11,12 5-(2-hydroxy-4-nitrophenylazo)thiorhodanine, 13 2-carboxyl-1-naphthalthiorhodanine, 14 5-(2-hydroxy-4-nitrophenylazo)-rhodanine, 15 5-(2hydroxy-5-nitrophenylazo)-rhodanine, 16 2-aminoacetophenone isonicotinoyl hydrazone, 17 ethopropazine hydrochloride and isothipendyl hydrochloride, 18 N,N-dimethylp-phenylene-diamine, 19 Nile blue, 20 Methylene blue 21 and 4-hydroxy-1-naphthalrodanine. 22 One interesting method described for the determination of gold utilised chemical amplification reactions based on oxidation with aqueous potassium periodate in a solution of gold(I), the masking of unreacted periodate with molybdate, and then the iodometric determination of the iodate and gold(III) produced.…”
Section: Introductionmentioning
confidence: 99%